Association of HMOX1 and NQO1 Polymorphisms with Metabolic Syndrome Components - Martínez-Hernández, Angélica; Córdova, Emilio J.; Rosillo-Salazar, Oscar; García-Ortíz, Humberto; Contreras-Cubas, Cecilia; Islas-Andrade, Sergio; Revilla-Monsalve, Cristina; Salas-Labadía, Consuelo; Orozco, Lorena (PLOS ONE, 2015)
Metabolic syndrome (MetS) is among the most important public health problems worldwide, and is recognized as a major risk factor for various illnesses, including type 2 diabetes mellitus, obesity, and cardiovascular diseases. Recently, oxidative stress has been suggested as part of MetS aetiology. The heme oxygenase 1 (HMOX1) and NADH:quinone oxidoreductase 1 (NQO1) genes are crucial mediators of cellular defence against oxidative stress. In the present study, we analysed the associations of HMOX1 (GT)n and NQO1 C609T polymorphisms with MetS and its components. Our study population comprised 735 Mexican Mestizos unrelated volunteers recruited from different tertiary health institutions from Mexico City. In order to know the HMOX1 (GT)n and NQO1 C609T allele frequencies in Amerindians, we included a population of 241 Amerindian native speakers. Their clinical and demographic data were recorded. The HMOX1 (GT)n polymorphism was genotyped using PCR and fluorescence technology. NQO1 C609T polymorphism genotyping was performed using TaqMan probes. Short allele (<25 GT repeats) of the HMOX1 polymorphism was associated with high systolic and diastolic blood pressure, and the T allele of the NQO1 C609T polymorphism was associated with increased triglyceride levels and decreased HDL-c levels, but only in individuals with MetS. This is the first study to analyse the association between MetS and genes involved in oxidative stress among Mexican Mestizos. Our data suggest that polymorphisms of HMOX1 and NQO1 genes are associated with a high risk of metabolic disorders, including high systolic and diastolic blood pressure, hypertriglyceridemia, and low HDL-c levels in Mexican Mestizo individuals.